2012
DOI: 10.1111/j.1365-2591.2012.02037.x
|View full text |Cite
|
Sign up to set email alerts
|

A biometric study of C‐shaped root canal systems in mandibular second molars using cone‐beam computed tomography

Abstract: The most prevalent configuration types were Melton's type I (coronal region) and type III (apical region). The linguo-central root area was the thinnest in C-shaped root canals of Korean mandibular second molars. These anatomical variations should be considered during surgical or nonsurgical endodontic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 34 publications
5
39
0
7
Order By: Relevance
“…13,14,18 The Chinese population also presented high prevalence of C-shaped canals, as reported by Yang et al, 12 Zheng et al 20 and Zhang et al 5 (32%, 39% and 29%, respectively). C-shaped root and canal configurations were seldom found in Caucasian populations: Cooke and Cox, 1 Weine 7 and Cimilli et al 8 reported a prevalence of 2.7%, 7.6% and 8.1% of C-shaped canals, respectively.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…13,14,18 The Chinese population also presented high prevalence of C-shaped canals, as reported by Yang et al, 12 Zheng et al 20 and Zhang et al 5 (32%, 39% and 29%, respectively). C-shaped root and canal configurations were seldom found in Caucasian populations: Cooke and Cox, 1 Weine 7 and Cimilli et al 8 reported a prevalence of 2.7%, 7.6% and 8.1% of C-shaped canals, respectively.…”
Section: Discussionsupporting
confidence: 51%
“…17 CBCT makes this canal system more predictable, and is a good option clinically speaking, because it can detect Cshaped canal configurations. 5,18 Today, some studies have been using micro-CT to investigate root canal morphology. 3,19 This evaluation provides accurate data, but micro-CT cannot be used clinically yet.…”
Section: Discussionmentioning
confidence: 99%
“…This canal system has the continuous isthmus connects individual root canals. 9 This morphology is most frequency seen in the mandibular 2nd molar and Asians. 10,11 Because of the complex of Cshape canal system, the comprehension of root canal anatomy is important for clinical dentists.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies evaluated the two-dimensional (2D) structure of the pulp cavity, other studies evaluated the 3D configuration of the same using extracted tooth samples injected with Indian ink and made transparent using methyl salicylate [125][126][127]. Recently, the detailed structure of the pulp cavity was elucidated using μCT and CBCT images [128][129][130][131][132][133][134][135]. These studies described the morphological complexity of the pulp cavity, particularly in root canals that often have a lateral and/or additional canal.…”
Section: Morphological Study Of the Pulp Cavitymentioning
confidence: 97%
“…The root canal system has been classified based on the canal pattern, and includes lateral branches, additional branches, and/or fused canals; the most popular criteria for the classification of root canals is the Vertucci's criteria [125,126]. A C-shaped root in the mandibular second molar is frequently found in the Japanese [130,131,[136][137][138][139][140] (reviewed by Kato et al [141]), and this unique root structure exhibits a complex root canal system.…”
Section: Morphological Study Of the Pulp Cavitymentioning
confidence: 99%